Cosmogenic nuclide measurements in southernmost South America and implications for landscape change - Kaplan, M.R. (2007)
We measured in situ 10Be, 26Al and 36Cl on glacial deposits as old as 1.1 Myr in the southernmost part of Patagonia and on northern Tierra del Fuego to understand boulder and moraine and, by inference, landscape changes. Nuclide concentrations indicate that surface boulders have been exposed for far less time than the ages of moraines they sit upon. The moraine ages are themselves constrained by previously obtained 40Ar/39Ar ages on interbedded lava flows or U-series and amino acid measurements on related (non-glacial) marine deposits. We suggest that a combination of boulder erosion and their exhumation from the moraine matrix could cause the erratics to have a large age variance and often short exposure histories, despite the fact that some moraine landforms are demonstrably 1 Myr old. We hypothesize that fast or episodic rates of landscape change occurred during glacial times or near the sea during interglacials. Comparison with boulder erosion rates and exhumation histories derived for the middle latitudes of semi-arid Patagonia imply different geomorphic processes operating in southernmost South America. We infer a faster rate of landscape degradation towards the higher latitudes where conditions have been colder and wetter.